Do Economic Literacy and Digital Literacy among Business Actors registered in the Grab Application Contribute to Entrepreneurial Behavior? - Annisa Paramaswary Aslam (Universitas Negeri Makassar, 2023)
This study aims to examine whether economic literacy and digital literacy among business people registered in the grab application contribute to entrepreneurial behavior. The type of approach used is a quantitative approach, the data source used is primary data with 97 respondents. The analysis method used is descriptive analysis and statistical analysis consisting of classical assumption test, multiple linear regression analysis, hypothesis testing, correlation analysis, coefficient of determination, validity test and reliability test. The results showed that there is a positive and significant relationship between economic literacy and digital literacy variables on entrepreneurial behavior. This means that economic literacy and digital literacy contribute to shaping entrepreneurial behavior in business actors registered in the Grab Application in Makassar City. These findings provide important implications for business actors in the culinary sector in Makassar city. In improving entrepreneurial behavior, they need to improve their understanding of economic concepts and make better use of digital technology. Participating in training and economic literacy programs can help business actors develop knowledge and skills relevant to the business world.